Work-family conflict and burnout among Chinese female nurses: the mediating effect of psychological capital - Wang Yang; Chang Ying; Fu Jialiang; Wang Lie (BMC, 2012)
Abstract Background Burnout among nurses not only threatens their own health, but also that of their patients. Exploring risk factors of nurse' burnout is important to improve nurses' health and to increase the quality of health care services. This study aims to explore the relationship between work-family conflict and burnout among Chinese female nurses and the mediating role of psychological capital in this relationship. Methods This cross-sectional study was performed during the period of September and October 2010. A questionnaire that consisted of the Maslach Burnout Inventory-General Survey (MBI-GS), the work-family conflict scale and the psychological capital questionnaire (PCQ-24) scale, as well as demographic and working factors, was distributed to nurses in Liaoning province, China. A total of 1,332 individuals (effective response rate: 78.35%) became our subjects. Hierarchical linear regression analyses were performed to explore the mediating role of psychological capital. Results Both work interfering family conflict and family interfering work conflict were positively related with emotional exhaustion and cynicism. However, work interfering family conflict was positively related with professional efficacy whereas family interfering work conflict was negatively related with it. Psychological capital partially mediated the relationship of work interfering family conflict with emotional exhaustion and cynicism; and partially mediated the relationship of family interfering work conflict with emotional exhaustion, cynicism and professional efficacy. Conclusion Work-family conflict had effects on burnout and psychological capital was a mediator in this relationship among Chinese nurses. Psychological capital was a positive resource for fighting against nurses' burnout.